Formation of Design Code and its Benefits for Humanity - ugli, Rakhmonov Nozimjon Nasrdin (European Journal of Life Safety and Stability (2660-9630), 2022)
This article deals with the Design Code and its purpose, tasks, formation processes, role in society, prevention of various rude waterfall actions of entrepreneurs by increasing economic efficiency and demand for quality customer service. It was noted that the set of requirements will have a significant impact on the current world ranking of developing Uzbekistan, as well as the culture of urban planning. It was noted that the implementation of such a set of projects by local authorities as a set of normative laws and regulations will have a positive impact on public life and increase the flow of tourists.